The role of Wnt signaling in hematopoietic stem cell development. (4th July 2017) - Richter, Jenna; Traver, David; Willert, Karl
Abstract: Hematopoietic stem cells (HSCs) can self-renew and differentiate into all cell types of the blood. This is therapeutically important as HSC transplants can provide a curative effect for blood cancers and disorders. The process by which HSCs develop has been the subject of extensive research in a variety of model organisms; however, efforts to produce bonafide HSCs from pluripotent precursors capable of long-term multilineage reconstitution have fallen short. Studies in zebrafish, chicken, and mice have been instrumental in guiding efforts to derive HSCs from human pluripotent stem cells and have identified a complex set of molecular signals and cellular interactions mediated by such developmental regulators as fibroblast growth factor, Notch, transforming growth factor beta (TGFβ), and Wnt, which collectively promote the stepwise developmental progression toward mature HSCs. Tight temporal and spatial control of these signals is critical to generate the appropriate numbers of HSCs needed for the life of the organism. The role of the Wnt family of signaling proteins in hematopoietic development has been the subject of many studies owing in part to the complex nature of its signaling mechanisms. By integrating cell fate specification with cell polarity establishment, Wnt is uniquely capable of controlling complex biological processes, including at multiple stages of embryonic HSC development, from HSC specification to emergence from the hemogenic epithelium to subsequent expansion. This review highlights key signaling events where specific Wnt signals instruct and guide hematopoietic development in both zebrafish and mice and extend these findings to current efforts of generating HSCs in vitro .